Heritability, pregnancy determination, and clinical follow-up in fetal copy number variation: an eight-year single-center retrospective study - Meiying Cai; Wenqi Chen; Meimei Fu; Liangpu Xu; Na Lin; Hailong Huang (Scientific Reports, 2026)
Abstract Copy number variation (CNV) is defined as a > 1-kb-long DNA fragment copy number increase or decrease, with fetal CNV judgment and genetic counseling posing difficulties. We tested and retrospectively analyzed fetuses using chromosomal microarray analysis (CMA), 169 with abnormal CNV being completely verified and followed up for pregnancy and postnatal outcomes. Among the 169 fetuses, 103 and 66 exhibited inherited and de novo CNV. Of the former, 50, 34, and 19 displayed hereditary pathogenic CNV (P-CNV) [likely pathogenic CNV (LP-CNV)], hereditary variants of uncertain significance (VUS), and hereditary benign (likely benign) CNV, respectively. Of the 50 fetuses with hereditary P-CNV (LP-CNV), 16, one, and two were terminated, died two days after birth, and retained abnormal postnatal phenotypes, respectively. Of the 34 fetuses with hereditary VUS CNV, 5 were terminated. Of the 19 fetuses with hereditary benign (likely benign) CNV, one was terminated and another died of heart disease after birth. Of the 66 fetuses with de novo CNV, 50, 13, and three had P-CNV (LP-CNV), VUS, and benign (likely benign) CNV, respectively. Of the 50 de novo P-CNV (LP-CNV) fetuses, 34 were terminated, one died after birth, and another was born with congenital heart defects. Of the 13 de novo VUS CNV fetuses, six were terminated. Finally, of the three de novo benign (likely benign) CNV fetuses, two were terminated and one displayed developmental delays after birth. This study highlights that CMA detects small, mostly inherited, P-CNV. Even P-CNV could yield favorable outcomes, while benign results do not preclude adverse events, especially with ultrasound anomalies. Evolving genomic data would refine CNV interpretation. Our findings enhance prenatal counseling by balancing the utility of inheritance information with prognostic uncertainty, supporting a personalized approach to genetic risk communication.